Coherent, correlated phenomena resulting from the incidence of high-energy leptons and photons on oriented crystals. - Vilakazi, Zeblon Zenzele (My University, 1998)
The scope of the research reported in this thesis addresses some phenomena associated with lepton-photon processes resulting from the incidence of ultra-relativistic particles upon highly ordered crystalline materials. The study of channeling phenomena were extended to investigate coherent, correlated and strong field versions of the basic QED processes at much higher energies and at incident angles slightly larger than the channeling critical angle. (Abbreviation abstract)
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Doctor of Philosophy.
Keywords: Leptons (Nuclear physics); Photons